DESIGNING AN INTERACTIVE LEARNING GAME INTEGRATING LOCAL CULTURAL VALUES TO ENHANCE JAVANESE SCRIPT LITERACY - Stiyas, Ayuk Susilaning; Subrata, Heru; Siswanto, M. Bambang Edi; Mariana, Neni; Rachmadyanti, Putri (STKIP PGRI Tulungagung, 2025)
Interactive Learning Games are one of the learning media used to measure the achievement of student learning objectives. This development research aims to test the feasibility of a product in the form of Interactive Learning Games to improve Javanese literacy. Validation testing was conducted by material experts, media experts, peer review, as well as testing on students with three types of tests including individual tests, small group trials, and large group trials. The Interactive Learning Games were created using Canva without requiring coding skills. The type of research is Research and Development using the ADDIE development model. The research target was grade V students at SDN Urangagung Sidoarjo. Based on the validation results from the media experts, the Interactive Learning Games received an average score of 92.6%, while the validation results from material experts received an average score of 90%. The product test results from peer review received an average score of 90.4% with some improvements, while individual trial tests obtained an average score of 91%, small group trials achieved an average of 87%, and large group trials reached 88%. Based on validation tests from experts, peer reviews, and trials conducted with students, the use of this Interactive Learning Game is feasible for use in the learning process and can also be used as independent assignments.